Glucagon-like peptide-1 receptor agonist activation ameliorates venous thrombosis-induced arteriovenous fistula failure in chronic kidneyd isease - Chien, Chiang-Ting; Fan, Shih-Chen; Lin, Shao-Chieh; Kuo, Chang-Chih; Yang, Chih-Hui; Yu, Tzu-Ying; Lee, Shih-Pin; Cheng, Dai-Yu; Li, Ping-Chia (Thrombosis and Haemostasis, 2014)
High shear stress that develops in the arteriovenous fistula of chronic kidney diseases (CKD) may increase H2O2 and thromboxane A2 (TXA2) release, thereby exacerbating endothelial dysfunction, thrombosis, and neointimal hyperplasia. We investigated whether glucagon-like peptide-1 receptor agonist/exendin-4, a potentially cardiovascular protective agent, could improve TXA2-induced arteriovenous fistula injury in CKD. TXA2 administration to H2O2-exposed human umbilical vein endothelial cells increased apoptosis, senescence, and detachment; these phenotypes were associated with the downregulation of phosphorylated endothelial nitric oxide synthase/heme oxygenase-1 (eNOS/HO-1) signalling. Exendin-4 reduced H2O2/TXA2-induced endothelial injury via inhibition of apoptosis-related mechanisms and restoration of phosphorylated eNOS/HO-1 signalling. Male Wistar rats subjected to right common carotid artery-external jugular vein anastomosis were treated with exendin-4 via cervical implant osmotic pumps for 16–42 days. High shear stress induced by the arteriovenous fistula significantly increased venous haemodynamics, blood and tissue H2O2 and TXB2 levels, macrophage/monocyte infiltration, fibrosis, proliferation, and adhesion molecule-1 expression. Apoptosis was also increased due to NADPH oxidase gp91 activation and mitochondrial Bax translocation in the proximal end of the jugular vein of CKD rats. Exendin-4-treatment of rats with CKD led to the restoration of normal endothelial morphology and correction of arteriovenous fistula function. Exendin-4 treatment or thromboxane synthase gene deletion in CKD mice markedly reduced ADP-stimulated platelet adhesion to venous endothelium, and prevented venous occlusion in FeCl3-injured vessels by upregulation of HO-1. Together, these data reveal that the use of glucagon-like peptide-1 receptor agonists is an effective strategy for treatment of CKD-induced arteriovenous fistula failure.
Keywords: Apoptosis; free radicals; peripheral vascular disease; glucagon-like peptide-1; thrombosis